2014
DOI: 10.1088/1674-4926/35/7/074005
|View full text |Cite
|
Sign up to set email alerts
|

Development of 10 kV 4H-SiC JBS diode with FGR termination

Abstract: The design, fabrication, and electrical characteristics of the 4H-SiC JBS diode with a breakdown voltage higher than 10 kV are presented. 60 floating guard rings have been used in the fabrication. Numerical simulations have been performed to select the doping level and thickness of the drift layer and the effectiveness of the edge termination technique. The n-type epilayer is 100 μm in thickness with a doping of 6 × 1014 cm−3. The on-state voltage was 2.7 V at JF = 13 A/cm2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In our previous research, a SiC SBD diode with a breakdown voltage higher than 10kV has been reported [1]. In this paper, we will report a 10 kV 4H-SiC diode with JTE termination.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our previous research, a SiC SBD diode with a breakdown voltage higher than 10kV has been reported [1]. In this paper, we will report a 10 kV 4H-SiC diode with JTE termination.…”
Section: Introductionmentioning
confidence: 89%
“…In most of the high voltage SiC SBD, the termination of floating guard ring termination (FGR) was widely used because that FGR can be formed together with active region [1]. However the protection efficiency of FGR is not enough for the ultrahigh voltage SiC power devices [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize this effect and to obtain a higher breakdown voltage, adequately designed edge termination structures should be applied. Nowadays, several edge termination structures have been adopted in the SiC power devices, such as field plate (FP), junction termination extension (JTE), and multiple floating field limiting rings (MFFLR) [4][5][6]. However, FP structures suffer from an enhanced oxide field near the field plate edge due to SiC's high critical field strength, resulting in serious reliability concerns in the high-voltage applications.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize this effect and to obtain a higher breakdown voltage, adequately designed edge termination structures must be applied. Nowadays, several edge termination structures have been adopted in the SiC power devices, such as field plate (FP), junction termination extension (JTE), and field limiting rings [4][5][6]. In the fabrication of high-voltage SiC devices, field plate and field limiting rings composite structure is more attractive since it is usually formed simultaneously with the main junction, and is not sensitive to the dose density.…”
Section: Introductionmentioning
confidence: 99%